The Expression and Clinical Significance of Different Forms of Mer Receptor Tyrosine Kinase in Systemic Lupus Erythematosus - Huaqun Zhu; Xiaolin Sun; Lei Zhu; Fanlei Hu; Lianjie Shi; Zhanguo Li; Yin Su (Journal of Immunology Research)
Objective. To investigate the expression and clinical significance of trans-membrane MerTK (mMer) on circulating CD14+ monocytes/macrophages and soluble MerTK (sMer) levels in plasma in systemic lupus erythematosus (SLE). Method. 108 SLE patients and 42 healthy controls were recruited in this study. The expression of mMer on the surfaces of CD14+ monocytes/macrophages was evaluated by flow cytometry (FCM). The sMer levels were measured by ELISA. Real-time quantitative PCR was applied to evaluate the mRNA levels of MerTK and ADAM17. Results. Both mMer expression on CD14+ monocytes/macrophages and sMer levels in plasma significantly increased in SLE patients compared to healthy subjects. The frequency of anti-inflammatory MerTK expressing CD14+CD16+ monocytes decreased in SLE. mMer expression was positively correlated with CD163 expression on CD14+ cells. Both the mMer expression on CD14+ monocytes/macrophages and sMer levels in plasma were positively correlated with SLEDAI. Furthermore, more elevated mMer and sMer levels were found in patients with higher SLEDAI, presence of anti-SSA, anti-Sm autoantibodies, and lupus nephritis. Conclusion. Both mMer and sMer levels significantly increased in SLE and positively correlated with disease activity and severity. The upregulation of MerTK expression may serve as a biomarker of the disease activity and severity of SLE.